2003
DOI: 10.1111/j.1540-5414.2003.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Team Leader Characteristics on Learning, Knowledge Application, and Performance of Cross‐Functional New Product Development Teams

Abstract: This study examines how leadership characteristics in new product development teams affect the learning, knowledge application, and subsequently the performance of these teams. Using data from a study of 229 members from 52 high-tech new product projects, we empirically demonstrate that team learning has a strong positive effect on the innovativeness and speed to market of the new products. Moreover, a democratic leadership style, initiation of goal structure by the team leader, and his or her position within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
364
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(389 citation statements)
references
References 102 publications
(209 reference statements)
15
364
2
8
Order By: Relevance
“…15 In fact, the participants' level of knowledge increased after practiced their role as primary service that be held by the researcher, so the participant had experience about how to take care of the mental illness patients in the community . Berends, Bij, and Weggeman argued that level of knowledge would increase if an individual obtained experience such as application of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…15 In fact, the participants' level of knowledge increased after practiced their role as primary service that be held by the researcher, so the participant had experience about how to take care of the mental illness patients in the community . Berends, Bij, and Weggeman argued that level of knowledge would increase if an individual obtained experience such as application of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of this study, we propose that the unique business environment of Ghanaian firms introduce some peculiarities into the ERP adoption and implementation process that has to be managed in order for high BPO to be obtained. Some of these important variables could include poor business ethics among Ghanaian businesses, culture of corruption (Transparency International, 2012), underdeveloped data culture (Hung and Chang, 2005), and weak organizational control (Cardinal, 2001;Sarin et al, 2003), which are not captured under any of the constructs identified in the research model that was tested. Further, firms in the banking and financial services industry, which dominated in our survey, are likely to be different from those in the manufacturing industry, which were used in the original study, in terms of how ERP systems are utilized in organizational processes.…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of their formal roles and charisma, transformational leaders have legitimacy and access to influential people and resources beyond their followers' reach (Sparrowe and Liden, 2005) and thus may be optimally positioned to obtain outside political support such as from government agencies and outside cooperation such as from suppliers and customers (Sarin and McDermott, 2003). Transformational leaders' reputation and prestige then gives TMT members outside legitimacy and trustworthiness, and increases their opportunities to build valuable social ties and extract their value (Burt, 1997).…”
Section: Tfl and Escmentioning
confidence: 99%